The Cropping Obstacle of Garlic Was Associated With Changes in Soil Physicochemical Properties, Enzymatic Activities and Bacterial and Fungal Communities - Yu, Jinyang; Liu, Yihao; Wang, Zuyu; Huang, Xiaohui; Chai, Dan; Gu, Yunfu; Zhao, Ke; Yu, Xiumei; Shuai, Zhengbin; Liu, Hanjun; Zhang, Xiaoping; Penttinen, Petri; et al. (Frontiers in Microbiology, 2022)
Abstract: Aims In garlic cultivation, long-time monoculture has resulted in continuous-cropping obstacles. However, the cause has not been studied to date. Methods We analyzed soils from garlic fields in Pengzhou, China, to determine continuous-cropping obstacle related changes in soil physicochemical properties and enzyme activities, and in the diversity and composition of bacterial and fungal communities. Furthermore, we examined the relationships between soil properties and the bacterial and fungal communities. Results The soil pH and the soil catalase, urease, invertase and polyphenol oxidase activities were lower in the cropping obstacle soil than in the healthy control soil. The richness and diversity of the bacteria were lower in the cropping obstacle soil than in the control. The bacterial and fungal communities in the cropping obstacle soil were clearly different from those in the control soil. The differences in bacterial communities between the cropping obstacle soil and the control soil were associated with differences in pH and available potassium content. The taxa with higher relative abundances in the cropping obstacle soils included potential plant pathogens and the taxa with lower relative abundances included potential plant growth promoters. Conclusions The enrichment of plant pathogens and the depletion of plant growth promoting fungi may have contributed to the poor growth of garlic in the cropping obstacle soil. The enzyme activity and microbial community differences were associated with acidification that was likely an important factor in the deterioration of the soil ecological environment and the garlic cropping obstacle. The results provide information to guide agricultural practices in cultivating garlic.